60-4t=

Simple and best practice solution for 60-4t= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 60-4t= equation:


Simplifying
60 + -4t = 0

Solving
60 + -4t = 0

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-60' to each side of the equation.
60 + -60 + -4t = 0 + -60

Combine like terms: 60 + -60 = 0
0 + -4t = 0 + -60
-4t = 0 + -60

Combine like terms: 0 + -60 = -60
-4t = -60

Divide each side by '-4'.
t = 15

Simplifying
t = 15

See similar equations:

| y=-x^2-6x+4 | | s-4t= | | 1-2x=1-3y | | 3*0-4*y=6 | | 0.63+0.24t=2.68t-1.20 | | 33u-50+u+29=29u | | -8w^2+18w-9=0 | | 6(y-1)-4=-4(-6y+3)-4y | | 2y+2(y-8)=6y-4(y-10) | | 8x^2+16x=192 | | 39q+19+30=44q+45 | | 0=-16t^2+150t+30 | | x^2-49x+500=0 | | 6a-47+30=5a | | y+3-2(-8y-3)=7(y-1) | | 3.8x-4.7=3.8x+17.5 | | 19-12x=151 | | 2a+36=4a-14 | | 2.67x+3x=102 | | (x-2)2+(y-4)2=36expand | | 5x+10=-26 | | 34616.0131=B*45.3 | | ln(4x)+1=3 | | (v+39)+5v=11v-36 | | 3679.6530=171.9464*h | | 5k-12=-22 | | -4x-16=-33 | | cbrt(x)+cbrt(x-16)=cbrt(x-8) | | 1378384.64=4534.16*h | | (x-2)2+(y-4)2=36 | | g(p+3)=2x^2+5x+2 | | 9x-5=32 |

Equations solver categories